Consumers' decisions to access or avoid added sugars information on the updated Nutrition Facts label. - Elizabeth Jiyoon Kim; Brenna Ellison; Brandon McFadden; Melissa Pflugh Prescott (PLoS ONE)
The Nutrition Facts (NF) label was recently updated and now includes the added sugars content in an effort to reduce added sugars consumption. This study investigated whether consumers wanted to access or avoid the added sugars content using an online experiment and five product categories (yogurt, cereal, fruit juice, snack bar, ice cream). We recruited a sample of 490 U.S. adults (49% female; 73% White/Caucasian). Respondents were randomly assigned to an information treatment (simple or full) before making decisions on whether to access or avoid the added sugars content. The simple information treatment explained that added sugars information was now available on the NF label, while the full information treatment included additional details (e.g., how to interpret the added sugars content and associated diseases). After making the access or avoid decisions for each product category, respondents rated their likelihood of purchase for ten products (two per category). Rates of information avoidance were much lower than what has been observed in previous studies, and rates of avoidance did not vary by information treatment. The majority of respondents (75-87% across the five product categories) preferred to access the added sugars content. Still, we found some consumers preferred to avoid this information, with higher rates of avoidance for the ice cream product category. Additionally, we found significant differences in likelihood of purchase ratings between information accessors and avoiders. Respondents who chose to access the added sugars information exhibited healthier purchasing behaviors for all product categories; they were more likely to purchase low added sugars products and less likely to purchase high added sugars products relative to information avoiders. Given consumers' demonstrated interest in accessing the added sugars content, it is important that the new changes to the NF label be broadly communicated to promote healthy eating behaviors.